A compositional shift in the soil microbiome induced by tetracycline, sulfamonomethoxine and ciprofloxacin entering a plant-soil system. (May 2016) - Lin, Hui; Jin, Danfeng; Freitag, Thomas E.; Sun, Wanchun; Yu, Qiaogang; Fu, Jianrong; Ma, Junwei
Abstract: Antibiotics entering the soil likely disturb the complex regulatory network of the soil microbiome, which is closely associated with soil quality and ecological function. This study investigated the effects of tetracycline (TC), sulfamonomethoxine (SMM), ciprofloxacin (CIP) and their combination (AM) on the bacterial community in a soil-microbe-plant system and identified the main bacterial responders. Antibiotic effects on the soil microbiome depended on antibiotic type and exposure time. TC resulted in an acute but more rapidly declining effect on soil microbiome while CIP and SMM led to a delayed antibiotic effect. The soil exposed to AM presented a highly similar bacterial structure to that exposed to TC rather than to SMM and CIP. TC, SMM and CIP had their own predominantly impacted taxonomic groups that include both resistance and sensitive bacteria. The antibiotic sensitive responders predominantly distributed within the phylum Proteobacteria . The potential bacteria resistant to each antibiotic exhibited phyla preference to some extent, particularly those resistant to TC. CIP and SMM resistance in soil was increased with exposure time while TC resistance gave the opposite result. Overall, the work extended the understanding of antibiotic effects on soil microbiome after introduced into the soil during greenhouse vegetable cultivation. Highlights: To describe soil microbiomes shifts induced by single- or multi-antibiotics. To characterize taxonomic groups predominantly impacted by TC, SMM and CIP. TC has a transient inhibition on soil microbiome than other antibiotics. CIP and SMM resistance were strengthened with exposure time increased. Effects of co-existence of TC, SMM and CIP on soil microbiome mainly source from TC. Abstract : Effects of antibiotics on soil microbiome depend on antibiotic type and exposure time, and each antibiotic has its own predominantly impacted taxonomic groups.